Paris 2024 Olympics: Diplomacy and Economic Prospects for France - Gustiawarman, Defri; Ul Husna, Anina (Department of International Relations, Hasanuddin University, 2025)
France is one of the great countries present in this world. The rapid progress that this country has itself is not without reason, reflecting on the historical record of how this country was able to influence the world through strong hegemony since hundreds of years ago and supported by stable politics and economy and the magnitude of France's role in the world makes the country quite respected. The development of an increasingly modern world has an impact on the massive development of science and technology as well, without exception to world politics, especially specifically with state diplomacy. The method used by the state to spread its wings of influence to the international world or commonly known as diplomacy has also experienced increasingly significant developments by presenting several other life-supporting elements that can be used as tools for the state to spread their wings of influence. One type of diplomacy that has massively occurred lately is sports diplomacy, as for what is meant by sports diplomacy here is the use of sports both techniques and sports events as a diplomatic tool to influence the world. This research itself applies the method of literature study and descriptive analysis aimed at examining how France's influence in using the Paris 2024 Olympics event as a tool of their sports diplomacy and the impact that comes from the international sporting event.